Indicador de Salubridade Ambiental: Estudo em um município de pequeno porte do Estado do Ceará - Lima, Denilson Nunes de Sousa (Universidade Federal Rural do Semi-Árido, 2021)
In 1999, the Technical Chamber of Planning of the State Council of Sanitation of the State of São Paulo (CONESAN) formulated the Environmental Health Indicator (ISA), covering qualitative and quantitative aspects of water supply services, sanitary sewage, public cleaning, drainage, vector control, water sources situation, besides a socioeconomic indicator of the municipalities. At the time of its creation, ISA-CONESAN had the purpose of measuring the sanitation conditions of each municipality in that state. After its creation, ISA-CONESAN started to be used in other regions of Brazil and, over time, ended up becoming a reference for several adaptations of the original formulation as suggested in its manual. In this context, the present work had the general objective of identifying the environmental health of the municipality of Beberibe, in the state of Ceará, through the determination of its ISA. The determination of the ISA of Beberibe was based on the proposal of Barreto (2020) who formulated the Environmental Salubrity Indicator adapted for small municipalities (ISA-MPP). The ISA-MPP has six first-order indicators: Water Supply Indicator (IAB), Sanitary Sewerage Indicator (HEI), Solid Waste Indicator (SWSI), Urban Drainage Indicator (UDI), Public Health Indicator (PSI) and Human Development Index (HDI). The result obtained for the ISA-MPP conferred a situation of average environmental salubrity for Beberibe, since the score value was 52.87, quite close to the lower limit for that class of salubrity (51 - 75) that made it possible to suggest the need for improvement of its indicator. Considering the importance of basic sanitation indicators in the ISA score and, consequently, in the health status of the municipality, as the municipality approaches the goals set out in its Municipal Sanitation Plan (PMSB), it is expected that its health status will be improved, and for this, there is also the need to establish public policies and a more efficient management
Keywords: Indicador Ambiental; Plano Municipal de Saneamento Básico; ISA-CONESAN; ISA-MPP; Environmental indicator; Municipal Sanitation Plan; ISA-CONESAN; ISA-MPP; ENGENHARIAS::ENGENHARIA CIVIL